Składnia słowa łacińskiego… J. Juraszka. Glosa do dziejów leksykografii łacińskiej w Polsce i na Śląsku (PDF 1,73 MB) (Książnica Śląska, 2025)
The subject of the text is a publication by J. Juraszek entitled “Składniasłowa łacińskiego w formie słownika” [Syntax of the Latin word in theform of a dictionary], which was published in Katowice in 1927. Thearticle contains its description and analysis from the point of view ofmetalexicographical knowledge. Among the major issues discussedare: the genological status of the work, the problem of its authorship,the relations to other pedagogical and lexicographical works and theauthor’s workshop. The observations reported on the technical andlinguistic layer of the publication allow us to propose the hypothesis that it was the result of a small-scale project, initiated by a privateauthor (teacher), who was deeply inexperienced in the art of dictionaries. However, the unprofessional nature and lack of advanced proofreading or further editorial care do not change the fact that “Syntaxof the Latin Word…” is the only Latin dictionary published in Katowice and Upper Silesia.